2013
DOI: 10.1002/ajoc.201300131
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azulene Derivatives That Have an Azathiacrown Ether Moiety and Their Selective Color Reaction Towards Silver Ions

Abstract: Azulene derivatives that have an azathiacrown ether moiety were synthesized by using a modification of the method described by Vögtle and co‐workers. These compounds are highly selective for detecting Ag+ ions, which is demonstrated visually by a color change from orange to violet. Structural studies of the Ag+‐induced colored product by NMR spectroscopy and ESI‐MS identified a 1:1 (Ag+:ligand) complex formed by the coordination of Ag+ ion with the azathiacrown ether moiety. Competition experiments in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This fact has been exploited for its use in a range of colorimetric sensors. Examples include sensors for silver (Wakabayashi et al, 2013), nitrite (Murfin et al, 2020), mercury (Wakabayashi et al, 2007(Wakabayashi et al, , 2008(Wakabayashi et al, , 2012Razus et al, 2011;Birzan et al, 2017;Buica et al, 2018Buica et al, , 2019, phosphate (Lichosyt et al, 2016(Lichosyt et al, , 2018, and reactive oxygen species (Murfin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This fact has been exploited for its use in a range of colorimetric sensors. Examples include sensors for silver (Wakabayashi et al, 2013), nitrite (Murfin et al, 2020), mercury (Wakabayashi et al, 2007(Wakabayashi et al, , 2008(Wakabayashi et al, , 2012Razus et al, 2011;Birzan et al, 2017;Buica et al, 2018Buica et al, , 2019, phosphate (Lichosyt et al, 2016(Lichosyt et al, , 2018, and reactive oxygen species (Murfin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the aforementioned reaction, the reaction of 6-bromoazulene 146 with two ester groups with amines yields the corresponding 6-aminoazulene derivatives 147 in good to excellent yields ( Scheme 49 ) [ 68 , 69 ]. The electrophilic substitution reaction of a derivative with a pyrrolidine substituent at the 6-position with bromine provides 2-bromo-6-pyrrolidinylazulene derivative 148 .…”
Section: Synthesis and Reactivity Of Azulene Derivatives With 4- mentioning
confidence: 99%
“…Whilst the azulene core has been incorporated into a wide variety of colorimetric chemical probes (exploiting the vivid colours it is famous for) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], this review will focus on those published probes that exploit the fluorescent nature of azulene. The nature of azulene fluorescence is highly dependent on substitution around the azulene core, which affects whether emission is more dominant from the S 2 or S 1 singlet excited state (a notable exception from this can be found in the work of Zhu et al, who showed that emission of azulene aldehydes can occur from the S 3 or S 2 excited state dependent on the nature of the hydrogen bonding present [ 31 , 32 ]).…”
Section: Introductionmentioning
confidence: 99%